Ultrasonic flow ratio measured immediately after successful rotational atherectomy with stent implantation predicts major adverse cardiovascular events - Zhao, Tao; Jin, Qing; Zhang, Xi; He, Jiaji; He, Guiping; Chen, Qiu; Sun, Yikang; Gan, Pin; Zhang, Jilei; Guang, Xuefeng; Xue, Qiang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe potential role of post-percutaneous coronary intervention (PCI) quantitative flow ratio (QFR) and ultrasonic flow ratio (UFR) in predicting adverse outcomes in patients with successful rotational atherectomy (RA) and stent placement remains to be defined.MethodsA total of 68 patients with highly calcific lesions, who underwent both QFR and UFR measurements after PCI with both RA and stenting, were enrolled. The major adverse coronary events (MACE) of 62 patients who completed 12-month follow-up were analyzed. The clinical characteristics of 9 patients with MACE and 53 non-MACE patients were compared. The predictors of MACE were analyzed using LASSO regression combined with Cox regression analyses.ResultsPatients with MACE had more lipid-rich and mixed plaques, less stent expansion and symmetry index, and lower post-PCI QFR and UFR compared with non-MACE patients. Cox regression analyses found that patients with lower post-PCI QFR (P < 0.05) or lower post-PCI UFR (P < 0.01) had a significantly higher risk of MACE. Lasso regression was performed to select the most important predictors, and the subsequent Cox multivariate regression analyses showed that post-PCI UFR, mixed plaque, and stent expansion index were independent predictors of MACE (all P < 0.05). Multivariate linear regression analyses also found that changes in UFR (P < 0.05) and post-PCI UFR at minimal stent area (P < 0.01) were significantly associated with post-PCI UFR results.ConclusionLower value of post-PCI UFR is an independent predictor of 12-month MACE after PCI with RA and stent implantation in patients with highly calcified lesions.